URGENSI KOMPETENSI PEDAGOGIK GURU DALAM MENCEGAH DEGRADASI MORAL SISWA DI SDN WANASARI 13 - Nurasrifha, Zahra; Yohamintin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses the urgency of teacher pedagogical competence in preventing moral degradation of students at SDN Wanasari 13. With the increasing challenges of negative behavior among students, such as bullying, decreased discipline, and lack of tolerance, the role of teachers as educators becomes very crucial. Pedagogical competence not only includes academic teaching, but also character development and moral values. Through an effective pedagogical approach, teachers can create a learning environment that supports positive values, such as empathy, cooperation, and discipline. This study used a qualitative method with interviews and observations as data collection tools, involving teachers and students. The results show that the implementation of good pedagogical competence can significantly reduce negative behavior and improve student morale. In addition, training and professional development for teachers need to be strengthened to ensure they have the necessary skills. Therefore, strengthening teacher pedagogical competence is very important to form a generation with noble character, improve the quality of education, and prepare students to face social challenges in the future.